(untitled) (Indian Journal of Arid Horticulture, 2025)
Among aromatic crops, mint (Mentha arvensis L.) is more popular in the country, as it is very economical crop and can be grown on variety of soils and climatic conditions, though it prefers well drained soils and humid conditions. At present, India is major producer of mint oil and menthol in the world. In Uttar Pradesh, mint is grown commercially in the Indogangatic plains of Rampur, Moradabad, Badaun, Bareilly and Barabanki districts. The menthol is major constituents of mint oil and has various uses in pharmaceuticals, cosmetics, flavours and confec- tionery industries. As a herbal drug, it is considered stimu- lant, stomachic and carminative.